2021
DOI: 10.1080/21655979.2021.1939636
|View full text |Cite
|
Sign up to set email alerts
|

Absent in melanoma 1-like (AIM1L) serves as a novel candidate for overall survival in hepatocellular carcinoma

Abstract: Identifying biomarkers for hepatocellular carcinoma (HCC) survival is of great importance for the early detection, monitoring, and predicting for prognosis. This study aimed to investigate the candidate biomarkers for predicting overall survival (OS) in HCC patients. Using RTCGAToolbox, top 50 upregulated differential expressed genes (DEGs) were identified. The least absolute shrinkage and selection operator (LASSO) and Cox models were used to select powerful candidate genes, and log rank method was used to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Molecular biomarkers may provide valuable information in the prognostic prediction of HCC. Zhou et al found that Absent in melanoma 1-like (AIM1L) could predict OS for HCC patients [ 22 ]. Recent studies have combined several molecular biomarkers to create predictive signatures [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular biomarkers may provide valuable information in the prognostic prediction of HCC. Zhou et al found that Absent in melanoma 1-like (AIM1L) could predict OS for HCC patients [ 22 ]. Recent studies have combined several molecular biomarkers to create predictive signatures [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this study also has limitations. First, this study’s analysis data come from public data resources such as TCGA, ICGC, and GEPIA ( 90 ). They lack their sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely noted that several genes are capable of being applied as promising diagnostic and prognostic biomarkers for HCC ( Jiang W. et al, 2021 ; Zhou et al, 2021 ). The association of identified TRIMs with clinicopathological factors and the prognosis of HBV-associated HCC was investigated.…”
Section: Discussionmentioning
confidence: 99%